Kinetic and Thermodynamic Studies of Cd2+, Cu2+ and Pb2+ Removal by Decanter Cake from Palm Oil Mill - Mohd Ridzuan, Nordin; Dewayanto, Nugroho; Liew, Kong Yong (SCUN, 2009)
Palm oil mills generate about 4-5 tons of decanter cake for every 100 tons of palm fresh fruit bunch processed. Due to the high organic content, the decanter cake could be converted into adsorbent for the removal of metal ions in waste water. The decanter cake was first dried at 105oC and then carbonized at 500oC. The resulting carbonized decanter cake was tested for removing Cd2+, Cu2+ and Pb2+ ions. Proximate analysis using thermogravimetry of decanter cake carbonized at 500oC indicated that the adsorbent contained 4% moisture, 21% volatiles, 23% fixed carbon, and 52% ash. Adsorption tests were carried out by mixing 1.0 g of decanter cake in 100 mL aqueous solution of various ions. Langmuir and Freundlich isotherm models were used to fit the isotherm experimental data. The maximum uptakes of Cd, Cu and Pb onto the carbonized decanter cake in this study were estimated to be 24, 23 and 97mg/g respectively. The adsorption kinetics was found to follow the pseudo second order kinetic model. Thermodynamic parameters including standard enthalpy. standard entropy and standard free energy were determined.